2007
DOI: 10.1523/jneurosci.1645-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Neurovascular Protection by Ischemic Tolerance: Role of Nitric Oxide and Reactive Oxygen Species

Abstract: Cerebral ischemic preconditioning or tolerance is a powerful neuroprotective phenomenon by which a sublethal injurious stimulus renders the brain resistant to a subsequent damaging ischemic insult. We used lipopolysaccharide (LPS) as a preconditioning stimulus in a mouse model of middle cerebral artery occlusion (MCAO) to examine whether improvements in cerebrovascular function contribute to the protective effect. Administration of LPS 24 h before MCAO reduced the infarct by 68% and improved ischemic cerebral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
117
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(127 citation statements)
references
References 70 publications
8
117
1
1
Order By: Relevance
“…Among the stimuli investigated for induction of tolerance are sublethal ischemia and proinflammatory mediators (Stagliano et al, 1999;Dawson and Dawson, 2000;Dirnagl et al, 2003;Kunz et al, 2007). Nitric oxide seems to have a major role in mediating ischemic tolerance induced by preconditioning.…”
Section: Nitric Oxide-role In Cerebral Ischemic Preconditioningmentioning
confidence: 99%
“…Among the stimuli investigated for induction of tolerance are sublethal ischemia and proinflammatory mediators (Stagliano et al, 1999;Dawson and Dawson, 2000;Dirnagl et al, 2003;Kunz et al, 2007). Nitric oxide seems to have a major role in mediating ischemic tolerance induced by preconditioning.…”
Section: Nitric Oxide-role In Cerebral Ischemic Preconditioningmentioning
confidence: 99%
“…Furthermore, we have demonstrated that the preconditioning protocol used is a safe and minor invasive procedure with no noteworthy postoperative morbidity, no signs of apoptosis in brain and no mortality. Several different preconditioning protocols have been described previously [6][7]12 . Others have used 6 min of BCCAO as a preconditioning stimulus [13][14] .…”
Section: Representative Resultsmentioning
confidence: 99%
“…Additionally, after removal of monofilaments CBF recovered to >90% of the respective baseline values after CCA occlusion. These LDF criteria are established in the literature and result in consistent infarct volumes 7 . We only included animals which had a Bederson score of at least of 1 after recovery from anesthesia after MCAO.…”
Section: Inclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Only few studies have investigated changes in CBF because of preconditioning before and at the time of subsequent ischemia. After preconditioning, some groups have found an increase in relative CBF, as determined from laser Doppler flowmetry, during or in the hours after subsequent ischemia, [32][33][34] whereas others observed neuroprotection without CBF effects during MCAO. [35][36][37] Dawson et al used autoradiography to show that 15 minutes after the onset of MCAO, CBF was unchanged in animals subjected to lipopolysaccharide preconditioning; however, 4 and 24 hours later, microvascular perfusion as assessed by an intravascular fluorescent tracer technique was preserved at higher levels in preconditioned animals compared with controls.…”
Section: Discussionmentioning
confidence: 99%